Improvement of Automatic Physics Data Analysis Environment for the LHD Experiment. (18th August 2018) - Emoto, M.; Suzuki, C.; Yokoyama, M.; Yoshinuma, M.; Seki, R.; Ida, K.
Abstract: The physical data of the Large Helical Device (LHD) project have been serviced by the Analyzed Data Server system, and approximately 600 kinds of physical data are served. In order to execute simulation programs for the LHD experiment, one must gather sets of physical data. Because the Automatic Analyzed Server (AutoAna) calculates the physical data automatically, it eases the scientist's task of collecting these physical data. The AutoAna has provided better computing environments for the scientists. Thus, the scientists, having recognized its benefits, make various requests as issues arise. In this paper, the authors introduce the current status of the AutoAna system.